Network Design and Management of User Bandwidth with Microtik in Communication and Informatics Office of North Sumatra Province - Tampubolon, Dedi Sanjaya; Hanifah Aprilyani; Pulungan, Ridho Wahyudi (Journal of Computer Science and Informatics Engineering, 2022)
A computer network is a group of computers that use communication protocols to communicate with each other and share data or information. The internet can also be interpreted as a computer network in a broader sense. The need for internet access is very high for users, making slow system performance to send data due to unstable internet conditions. Therefore, in regulating and limiting the use of internet bandwidth, it is indeed an important thing when the internet connection is limited, for example, the limited bandwidth quota from the ISP. We need to limit the bandwidth quota for each user connected to the mikrotik router. On the mikrotik router itself, there are features that can limit (limit) bandwidth, namely queue. By using the simple queue and queue tree methods, you candesigning bandwidth restrictions that make internet conditions in a company can be maintained and more stable due to bandwidth restrictions for each user who use the internet.